Seeking Allah, finding Jesus : a former Muslim shares the evidence that led him from Islam to Christianity : study guide : eight sessions /: a former Muslim shares the evidence that led him from Islam to Christianity : study guide : eight sessions. ([2016]) - Qureshi, Nabeel; Harney, Kevin; Harney, Sherry, 1960-
No abstract available